Foliar epidermal, stem and petiole anatomy of Meghalayan Dioscorea L. (Dioscoreaceae) and its systematic implication (Bangladesh Journal of Plant Taxonomy, 2017)
A comparative anatomical study of eight species of Dioscorea L. from Meghalaya, North East India was carried out in order to evaluate the taxonomic significance of anatomical characters to differentiate the species. Characters were coded and analyzed by PCA and cluster analysis. The combination of selected qualitative and quantitative anatomical characters of foliar epidermis, stem and petiole were significant for identification of species. The characters that contributed most to the separation of the species were type of stomata, length of stomata, stomatal index, leaf epidermal hairs, stem epidermal hairs, layer of stem sclerenchyma, number of vascular bundle in outer ring and inner ring of stem, paired or unpaired metaxylem, presence of phloem at both ends or at one end, presence or absence of starch grain in stem, petiole epidermal hair and presence or absence starch grain and crystal in petiole. An indented dichotomous key based on anatomical characters was constructed to distinguish and identify the species.Keywords: Anatomy; Dioscorea; Cluster Analysis; Principal Component Analysis; Systematics.Bangladesh J. Plant Taxon. 24(1): 5363, 2017 (June)